2011
DOI: 10.1177/0887403411388405
|View full text |Cite
|
Sign up to set email alerts
|

Probation Recommendations and Sentences Received: The Association Between the Two and the Factors That Affect Recommendations

Abstract: Although an association has been established between sentencing recommendations made by probation officers and the actual sentences received by offenders, to date, few scholars have examined the role of offender and officer characteristics in these recommendations. This article uses quantitative data from one small California jurisdiction between 2004 and 2006 to explore the role of legal and extralegal factors in sentencing recommendations. The minimal impact of extralegal factors is discussed and conclusions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(32 reference statements)
0
4
0
1
Order By: Relevance
“…Normally in the form of observations, file reviews, interviews, and questionnaires (including simulations) 15 There are some important exceptions to this claim. See for exampleMyers and Talarico (1987) where the authors gathered over 27,720 offenders, orHood (1992), who compiled a sample of 3,317 defendants.16 Such as the new General Data Protection Regulation in operation in the whole of the European Union since the 25th-May-2018.17 Available online here https://www.sentencingcouncil.org.uk/analysis-and-research/crown-court-sentencingsurvey/record-level-data/ and here https://www.gov.uk/government/collections/criminal-justice-statistics.18 Available online here https://www.ussc.gov/, here http://pcs.la.psu.edu/, and here https://mn.gov/sentencingguidelines/.19 This process should also be applied to record other actors that have been shown to influence sentencing decisions such as prosecutors and probation officers(Goulette et al, 2015;Leifker and Sample, 2011;Spohn et al, 2017;Sutton, 2013;Wooldredge, 2012).…”
mentioning
confidence: 99%
“…Normally in the form of observations, file reviews, interviews, and questionnaires (including simulations) 15 There are some important exceptions to this claim. See for exampleMyers and Talarico (1987) where the authors gathered over 27,720 offenders, orHood (1992), who compiled a sample of 3,317 defendants.16 Such as the new General Data Protection Regulation in operation in the whole of the European Union since the 25th-May-2018.17 Available online here https://www.sentencingcouncil.org.uk/analysis-and-research/crown-court-sentencingsurvey/record-level-data/ and here https://www.gov.uk/government/collections/criminal-justice-statistics.18 Available online here https://www.ussc.gov/, here http://pcs.la.psu.edu/, and here https://mn.gov/sentencingguidelines/.19 This process should also be applied to record other actors that have been shown to influence sentencing decisions such as prosecutors and probation officers(Goulette et al, 2015;Leifker and Sample, 2011;Spohn et al, 2017;Sutton, 2013;Wooldredge, 2012).…”
mentioning
confidence: 99%
“…In general, studies of professionals have found that extraneous factors can affect the extent to which personal biases influence evaluator discretion when using other types of assessments. Examples include the evaluators’ discipline (e.g., social worker, psychologist, or psychiatrist; Murrie et al, 2008); the party retaining the evaluator, be it the prosecution or defense (Murrie et al, 2009); the ambiguity of evidence (Charman et al, 2017); and years of experience, such that less experienced probation officers tend to be more lenient in their sentencing recommendations than veteran probation officers (Leifker & Sample, 2011).…”
Section: Factors Influencing Evaluator Biases In Decisionsmentioning
confidence: 99%
“…A common, yet spurious, measure widely used to measure influence, is the correlation between sentencing decisions recommended by Reports and the actual sentence passed. Variously referred to as ‘concurrence’, ‘concordance’, or ‘agreement’, as if evidencing one‐way causality, Reports are assumed to have influenced the sentence outcome they suggested (for example, Cole and Angus , p.302; Deane , p.93; Leifker and Sample ; Taylor, Clarke and McArt ). The co‐incidence of a recommendation and sentencing outcome is conflated with judges ‘agreeing with’ the recommendation, or elsewhere as ‘following’ the recommendation (Birkett , p.500).…”
Section: The Quality Of Reports In the Consumerist Logicmentioning
confidence: 99%
“…Carter and Wilkins () made the point some 50 years ago: ‘Probation officers write their reports and make recommendations anticipating the recommendation the court desires to receive’ (p.508, italics added). Nevertheless, the belief that co‐relation evidences corresponding influence on the sentencing outcome is surprisingly difficult to dislodge, with some papers (for example, Leifker and Sample ) even citing Carter and Wilkins's article in support of the very supposition which they dismantled.…”
Section: The Quality Of Reports In the Consumerist Logicmentioning
confidence: 99%